Analysis of Factors Related to Work Stress in Workers at PT. Hisar Makmur - Wijaya, Tanya Jewel Christabel; Sinolungan, Jehosua Samratson Victor; Verronica Joyce Lapian, Stanss Levyna Hermien (Pelopor Publikasi Akademika, 2025)
The purpose of this study is to analyze factors related to work stress in workers at PT. Hisar Makmur. This research is a quantitative research with an analytical observational research type using cross sectional study research design. This research was conducted on the Construction Work Project of PT. Hisar Makmur, Construction of the Integrated Lecture Building of IAIN Manado located in Wori District, North Minahasa Regency, in January - March 2025. The respondents in this study were 93 respondents. The independent variables in this research are workload, work fatigue, age, and salary satisfaction. The dependent variable in this research is work stress. The data analysis conducted was univariate which explains the frequency distribution of research variables, bivariate analysis using the Chi-Square test, and the multivariate analysis using the Multiple Logistic Regression test. The result of the bivariate analysis using Chi-Square test showed that there is a significant relationship between workload and work stress (p=0,001), there is a significant relationship between work fatigue and work stress (p=0,000), there is no relationship between age and work stress (p=0,808), and there is a significant relationship between salary satisfaction and work stress (p=0,011). The result of the multivariate analysis show that the work fatigue variable has the most dominant infuence on work stress with an Exp(B) value of 12,200, which means that respondents who experience work fatigue are 12,2 times more at risk of experiencing work stress. The conclusion of this research is that workload, work fatigue and salary satisfaction are related to work stress in workers at PT. Hisar Makmur. While age is not related to work stress in workers at PT. Hisar Makmur.